2020
DOI: 10.1080/26895269.2020.1848691
|View full text |Cite
|
Sign up to set email alerts
|

Transgender women of color in the U.S. South: A qualitative study of social determinants of health and healthcare perspectives

Abstract: Background: Research has shown that transgender and nonbinary people experience health disparities. However, few studies have explored, in-depth, the health-related experiences, perceptions, needs, and priorities of transgender women of color living in the U.S. South, a region that poses unique challenges to achieving health for transgender people. Aims: This study explored the social determinants of health, healthcare experiences, and health-related priorities of trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 42 publications
(48 reference statements)
0
26
0
Order By: Relevance
“…Only four studies (Cahill et al., 2020; Fabbre & Gaveras, 2020; Grzanka et al., 2020; Smart et al., 2020) used qualitative methods to examine state‐level policies and one used a mixed‐methods design (Currin et al., 2019). In qualitative interviews, transgender women discussed the importance of private and public insurance coverage of PrEP medications for adherence and acceptance (Cahill et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only four studies (Cahill et al., 2020; Fabbre & Gaveras, 2020; Grzanka et al., 2020; Smart et al., 2020) used qualitative methods to examine state‐level policies and one used a mixed‐methods design (Currin et al., 2019). In qualitative interviews, transgender women discussed the importance of private and public insurance coverage of PrEP medications for adherence and acceptance (Cahill et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
“…In qualitative interviews, transgender women discussed the importance of private and public insurance coverage of PrEP medications for adherence and acceptance (Cahill et al., 2020). Fifteen transgender women in the Southern United States reported that state laws restricting bathroom use based on sex identification led to policing of behavior and stress for TGNC adults (Smart et al., 2020). Moreover, in the LGBTQ+ community, state laws allowing the denial of counseling services to any client on the basis of “sincerely held principles” contribute to feelings of unsafety, the avoidance of help‐seeking behavior, and concerns that other anti‐LGBTQ+ laws would soon follow (Grzanka et al., 2020).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is important to note that these reviews draw from literature ranging from 2008 to 2018. However, the studies on TGD experiences with healthcare or provider knowledge published more recently continue to find similar barriers including mistrust in systems, structural barriers, difficulty finding competent providers, and the importance of gender-affirming environments [ 6 – 9 ]. More empirical research is needed on the specific steps of mental health help-seeking for TGD adults as well as increased attention to barriers and facilitators for a variety of mental health treatment models, such as inpatient settings, and experiences of underserved TGD communities.…”
Section: Reviews Of Barriers and Facilitators To Mental Health Carementioning
confidence: 99%